(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Our vocational training system is changing constantly, nevertheless, the process cannot ignore the assessment of the results reached so far and the channelling of the participating partners’ feedback, and the elaboration of newer developmental or correctional steps based on them. The main aim of our present research was to study the expectations related to the world of work of given professional groups on different levels of vocational training, the role and function of employers in the vocational training process. After the exploration the aim of the research was to give voice to professional recommendations, which can be a solution for adjusting a problem of education/vocational training to the labour market’s problems on a qualification level.